Community Education and Empowerment in Handling Dengue Fever in Kurung Kejayan Village, Pasuruan - Miftahillah Miftahillah; M. Mujib Utsmani; Siti Khudoibah (Future Tecno-Science Publisher, 2025)
Dengue fever (DHF) is still a public health problem in many parts of Indonesia, including Kurung Village, Kejayan Subdistrict, Pasuruan District. The low awareness of residents towards environment-based prevention behavior is one of the factors for the high risk of transmission. This activity aims to increase knowledge, establish clean and healthy living behavior (PHBS), and build a community-based dengue prevention system through education and community empowerment. Through participatory and educative methods, this activity resulted in increased community knowledge, changes in 3M Plus behavior, and the implementation of routine PSN at the RT level. The program also strengthens collaboration between the community, village government, and Puskesmas. Theoretically, this activity supports the community empowerment approach, the Health Belief Model, and the socioecological model, and has proven effective for replication in other areas.